Engineering of Coffee Waste Based Drainage Filtration Media on Polyester Fabric for Green Infrastructure Applications - Muchamad Yafis; Jibril Maulana; Rizka Sarah H. F. A.; Dewi ‘Izzatus Tsamroh (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The growing pressure on urban drainage systems caused by blockages and environmental pollution highlights the importance of developing sustainable filtration materials. This study explores the use of coffee waste as an environmentally friendly filler integrated into polyester fabric (PE 24S) to create a green filtration medium for drainage applications. The research focuses on developing and characterizing the composite material through macro-photographic morphology analysis, tensile strength testing, and antibacterial evaluation. The findings demonstrate that polyester fabric modified with coffee waste shows a tensile strength of 54.024 ± 5.498 MPa, elongation of 111.128 ± 6.915%, and a Young’s modulus of 0.486 ± 0.543 MPa, indicating improved flexibility and sufficient mechanical durability for drainage system use. Additionally, antibacterial testing reveals that the composite material can inhibit microbial growth due to the presence of natural bioactive compounds found in coffee waste. Overall, the results suggest that coffee waste–enhanced polyester fabric offers a sustainable and mechanically reliable alternative for environmentally friendly drainage infrastructure while supporting circular economy practices.